Desenvolvimento de um sensor de salinidade utilizando redes de Bragg corroídas em fibra óptica - Zanella, Fellipe Meneghim (2021)
The measurement of salt concentration in brine tanks is done manually and with limited accuracy. Generally, the Baumé areometer is used, 1 ºBe in its scale can lead to an error of approximately 1% in the salt concentration, due to the associated parallax error in the reading of the meniscus of the sample taken from the brine. One solution to be exploited for these disadvantages would be the use of optical sensors such as FBGs, which can be used to improve accuracy and provide real-time monitoring of variations in salt concentration. The salt concentration is one of the most important physicochemical parameters in the quality control of cheeses that use the brine salting process, which is measured in dairy tanks used in cheese production. In this work, two EFBGs (etched fiber Bragg gratings) with the same characteristics that were recorded in single mode fibers, both sensitive to variation of refractive index, were used to measure the levels of salt concentration in a solution of brine, relating the salt concentration and temperature with the Bragg wavelength shift. For the tests, the sensor was immersed in a beaker with an already homogeneous brine solution (NaCl + H2O), which was placed inside a thermal circulator in an adiabatically isolated compartment with fixed temperature, the concentration measurements were performed with the aid of a Baumé areometer. Two tests were carried out, one with a temperature of 10 ºC and at 20 ºC, the variation of the Bragg wavelength generated by the variation in the concentration of salt for the tests performed, showed that the relationship between them is not linear. With increasing temperature from 10 ºC to 20 ºC the sensitivity was from 0.0169 nm/% to 0.0207 nm/% showing greater sensitivity with increasing temperature.